Detektor Banjir Dan Edukasi Kesadaran Bencana Banjir Desa Bakalan Rayung Kudu Jombang - Sa'adah, Lailatus; Mahendri, Wisnu; Alwi, Joni; Ansori, M. Rizal Ma’ruf; Syafa’ah, Alya Fitriani; Firosulhaq, Muhammad; Alfatih, Ahmad Daud; Huda, Saihul Atho Alaul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This project focuses on the development of flood detectors and disaster awareness education programs as a disaster mitigation effort in flood-prone areas. The main objective of this project is to create a reliable and effective flood detection system to provide early warning to the community in Bakalanrayung village, thereby reducing the potential for material damage and loss of life caused by flooding. The approach used in this project combines modern sensor technology with narrative methods in disaster awareness education. Ultrasonic sensors are installed at strategic locations to monitor water levels in real time, and the system is directly connected to the Telegram application to automatically send alerts when water levels reach critical thresholds. In addition, the education program is carried out through interactive sessions designed to increase community awareness and preparedness for flood disasters. This education uses strong narratives and visual materials to help communities understand the risks associated with flooding and the steps they should take to protect themselves and their families. The results of this project show a significant increase in the level of community awareness of flood risks and their response time to flood warnings, which ultimately contributes to reducing the negative impacts of flood events in the area. Integration of flood detection technology with community education programs has proven effective in improving disaster preparedness.